Implementation of Business Model Canvas Development (Case Study : Beauty Clinic dr.Reni.G) - Luzi Zafriana (Tibuana, 2022)
As one of the business development strategies, dr. Reni. G made improvements by remodeling its business model. This study uses a descriptive analysis methodology on the case study of the Beauty Clinic of dr. Reni. G. After conducting the literature study, interview process, Focus Group Discussion, and observation, then a SWOT analysis was carried out to determine the uniqueness of dr. Reni. G to be in line with the capabilities of existing resources. The results of the SWOT analysis in quadrant I (1.662602; 1.777778), showed that the Beauty Clinic dr. Reni. G requires a progressive strategy. To be able to achieve the expected performance targets and profit, it is important to immediately implement improvements to the nine elements of the Business Model Canvas in the Beauty Clinic of dr. Reni. G